Sensory traits, color, and shelf life of low-dose irradiated, precooked, ground beef patties - Luchsinger, S.E.; Kropf, Donald H.; Garc a Zepeda, C.M.; Marsden, James L.; Hunt, Melvin C.; Hollingsworth, M.E.; Stroda, Sally L.; Chambers, Edgar, IV; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Irradiation did not influence bitter, bloody, burnt, chemical, fat-like, juiciness, liver-like, beef identity, metallic, rancid, sour, sweet, and toughness flavor/textural attributes, beef aroma, or off-odor in precooked ground beef patties. Irradiation slightly increased the animal hair flavor note, but intensity levels were <1 on the 15-point sensory scale. Except for 10% fat non-irradiated controls, reheated precooked patties had a slight sour, ammonia-like, top note. Irradiation at 3.5 kilograys (kGy) increased external redness in vacuum-packaged patties, but not in aerobic packages. Aerobic packaging with or without irradiation decreased external precooked redness. Oxidative rancidity increased when patties were irradiated in aerobic but not in vacuum packages. Reduction of oxygen in vacuum bags extended the shelf life of the precooked ground beef patties, at least in terms of oxidative rancidity. Precooking ground beef patties, irrespective of irradiation or packaging type, posed sensory disadvantages, and improvements to the precooking process are needed before irradiating at low-dose levels is appropriate.
Keywords: Beef; Irradiation; Ground beef; Precooked; Sensory; Color